АДАМ ГЕЎДЕСИН СЫЗЫП ҮЙРЕНИЎДЕ ҚЫСҚА МҮДДЕТЛИ ҚАРАЛАМАЛАРДЫҢ ӘҲМИЙЕТЛИЛИГИ - Бекмуратов, Т. (ILIM hám JÁMIYET, 2019)
The article deals with the discussion of the role and importance of some training lessons in teaching drawing the human body. In addition to this, it also gives the historical data on the proportions of sizes of human body.